Evaluation and improvement of the novel method for vitrification of a few human sperms. (September 2019) - Li, Yuhu; Ma, B.; Yu, Ping
Abstract: Research question: The purposes of this study are to evaluate the performance of the novel SpermVD device on vitrification of a few human sperms, and determine whether PICSI dish and density gradient centrifugation can improve the quality of sperm after thawing. Design and methods: In order to determine the suitable preparation methods, both washed sperm and neat sperm were selected in ICSI dish and PICSI dish, and frozen with the novel SpermVD device. The selected sperms were transferred to freezing droplets with 1 μl droplet of a 50/50 v/v mixture of QA Sperm Freezing Medium and QA Medium w/Hepes on the SpermVD wells. And the device was exposed to vapor of liquid nitrogen for 5 min and then placed into LN2 immediately. The sperms were thawed in a 37℃ oil filled dish which contained QA Medium w/Hepes droplets and they were searched and revaluated immediately. The frozen effects of sperm were evaluated by progressive motility, motility, viability and recovery rates of freezing-thawing sperm. Results: After freezing-thawing, the overall sperm recovery rate was 94.2% with 70% viability, 20.7% progressive motility, and 36.2% motility. The progressive motility, motility, viability and recovery rates of washed sperm were lower than that of the neat sperm, with a significant difference ( P < 0.01) at both viability and motility rates. In addition, the viability rate was significantly higher in PICSI dish group than that of ICSI dish group ( P < 0.01) and the motility, recovery and progressive motility rates were not significantly different between the two groups ( P > 0.05). Conclusions: The spermVD device was one of the effective platforms for freezing a few human sperms and using PICSI dish to select mature neat sperms could improve the quality of sperm after thawing. Density gradient centrifugation might be not required or suitable sperm preparation methods before freezing.